Cultura de segurança da informação: um processo de mudança organizacional na Petrobrás - Vieira, Patrícia dos Santos (2009)
This study aims to verify whether and to what degree the criteria proposed by Kotter to the implantation of an information security culture were attended at Petrobras. Petrobras, for several years, was an oil country-wide state company. As in several other companies, with the internationalization process, more players with interests in valuable information started interacting with the company. The necessity of conducting a change management process to implant an information security culture was verified. The model defined by Kotter has eight steps that, if followed, guarantee a successful change. In order to achieve the study’s purpose, bibliographic research and Petrobras’ files and documents research and field research were done. The period of study was from 2002 until 2009. The process evaluation has shown some fails at the steps defined by Kotter. It is possible to mention: high complacency; sense of urgency attributed only in the first moment; long-term vision was not widely declared; the reason of change was not explicit throughout time; information security organization structure in the fields is still deficient; there was not complete alignment of the company’s management systems; the existence of structures and systems that make the evaluation of the actions and the recognition of the people involved in the cultural change process more difficult; and lack of worrying in commemorating short-term achievements.